Dimerization of the type IV pilin from Pseudomonas aeruginosa strain K122-4 results in increased helix stability as measured by time-resolved hydrogen-deuterium exchange - Cristina Lento; Derek J. Wilson; Gerald F. Audette (Structural Dynamics, 2016)
Truncated pilin monomers from Pseudomonas aeruginosa strain K122-4 (ΔK122) have been shown to enter a monomer-dimer equilibrium in solution prior to oligomerization into protein nanotubes. Here, we examine the structural changes occurring between the monomeric and dimeric states of ΔK122 using time-resolved hydrogen-deuterium exchange mass spectrometry. Based on levels of deuterium uptake, the N-terminal α-helix and the loop connecting the second and third strands of the anti-parallel β-sheet contribute significantly to pilin dimerization. Conversely, the antiparallel β-sheet and αβ loop region exhibit increased flexibility, while the receptor binding domain retains a rigid conformation in the equilibrium state.